Characterization of Aluminum Contacts on Cobalt Oxide Films Grown with Different Oxygen Concentrations - Angelico, João C. [UNESP]; Neto, Nilton F. A. [UNESP]; Da Silva, José H. Dias [UNESP] (Springer Nature, 2019)
The electronic transport in a metal/semiconductor/metal (MSM) structure, consisting of cobalt oxide films with aluminum (Al) contacts, was investigated. The cobalt oxides were grown by direct current (DC) magnetron sputtering using different oxygen gas flow rates. The behavior of the electric conductivity in the 200 K–350 K temperature range, the Schottky barrier heights (∅ B) and specific contact resistances (Rc) were investigated. The analysis shows that small oxygen flow variations produce significant changes in electrical characteristics of the MSM structure.
Keywords: electrical conductivity; Schottky barrier; thin films